Keadaan Psikologis Mahasiswa Kedokteran Gigi Universitas Sumatera Utara yang Sedang Melaksanakan Pembelajaran Daring - Shabrina Alifah Siregar; Gema Nazri Yanti (Syntax Corporation Indonesia, 2024)
This study aims to identify the characteristics of students during online learning, as well as evaluate their state and level of stress, anxiety, and depression using the Depression Anxiety and Stress Scale (DASS). This research is a descriptive survey research, namely to find out the psychological state of students of the Faculty of Dentistry, University of North Sumatra who are carrying out online learning using the depression anxiety stress scale questionnaire (DASS-42) which consists of stress, anxiety, and depression. This research was conducted at the Faculty of Dentistry, University of North Sumatra which is located in Medan City, North Sumatra Province. This research was carried out from June 2021 to July 2021. Results, In terms of anxiety, 74.5% did not have difficulty swallowing, and moderate anxiety was the highest (31.2%). For depression, 66.8% did not feel that their lives were meaningless, with normal depression being the highest (50.6%). Stressors include learning tasks (72.5%), unavailability of practical tools (64.4%), limited internet quota (61.1%), and boredom with online learning (48.2%).